Cholesterol-lowering activity of lactic acid bacteria probiotic strains in vivo - Starovoitova, Svitlana; Babenko, Lidia; Timoshok, Natalia; Shynkarenko, Lyubov; Lazarenko, Lyudmila; Spivak, Mykola (My University, 2012)
Cholesterol-lowering activity of probiotic strains of lactic acid bacteria genera Lactobacillus and Bifidobacterium in the in vivo experiments on the model of experimental hypercholesterolemia in mice was studied. It is established that the prophylactic scheme of introduction of probiotic cultures is more effective than therapeutic one for the manifestation of cholesterase activity of probiotic cultures. The most effective were the cultures: L. acidophilus and B. bifidum, as well as the composition B. bifidum + B. longum. Cholesterol-lowering activity of the studied strains and their compositions in this experiment ranged between 40-78%. It is noted that cholesterase activity of other studied strains was not lower, and in some cases, higher than that of most of the drugs currently used in cholesterinosis.
Keywords: probiotic lactic acid bacteria; cholesteraze activity; cholesterol-assimilating strains; пробіотичні молочнокислі бактерії; холестеразна активність; холестерин-асимілюючі штами; кафедра біотехнології і мікробіології